2021
DOI: 10.5539/hes.v11n1p121
|View full text |Cite
|
Sign up to set email alerts
|

How is Academic Performance Affected by Delay in Student Loan Disbursement in Kenyan Universities? A Case Study of Kenyatta University

Abstract: The current research focused on the impact of delayed loan disbursement on performance. The study focused on Kenyatta University, situated in Nairobi, Kenya. In the study, the variables of class attendance, personal expenses, and course registration were evaluated as the main factors that impacted student performance due to delayed loans. A sample of 196 students were randomly selected from the population to take part in the study. The students were given questionnaires regarding higher education loan disburse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The study observed a systemic increase in deferments as students progress to the third and fourth years of their study. Bomer et al (2021) study on the impact of delayed loan disbursement on university students' academic performance in a university in Kenya found that students who experienced loan delays had problems covering their personal expenses, registering for courses, and attending classes. These challenges had a significant impact on the final performance in terms of grade point average.…”
Section: Introductionmentioning
confidence: 99%
“…The study observed a systemic increase in deferments as students progress to the third and fourth years of their study. Bomer et al (2021) study on the impact of delayed loan disbursement on university students' academic performance in a university in Kenya found that students who experienced loan delays had problems covering their personal expenses, registering for courses, and attending classes. These challenges had a significant impact on the final performance in terms of grade point average.…”
Section: Introductionmentioning
confidence: 99%